2009
DOI: 10.1182/blood-2008-07-166389
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor c-Myc enhances KIR gene transcription through direct binding to an upstream distal promoter element

Abstract: 4,5 Therefore, an elucidation of the factors that influence KIR gene transcription and a more thorough understanding of how KIR signaling affects NK-cell development are needed to understand how to manipulate the innate immune system for therapeutic purposes.Progress in the elucidation of how KIR genes are regulated has been limited because of the complexity of the KIR gene locus and the fact that KIR genes are not present in model rodent species, which are amenable to genomic manipulation. The conventional 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 46 publications
6
53
1
1
Order By: Relevance
“…Therefore, we cannot exclude that some NK cells have received in vivo an additional signal leading to the initiation of KIR expression and that cytokines would only promote the preferential expansion of this committed subset in vitro. However, a recent report from Cichocki et al demonstrated that IL-15 or IL-2 induce c-Myc binding to an upstream distal KIR promoter element that promotes KIR transcription [14], supporting the idea that cytokines are directly required for induction of KIR expression and do not only allow the proliferation/differentiation of a subset of committed NK cells. Even if we cannot rule out that further unknown signals might be required, our data clearly show that cytokines are essential to induce stable KIR de novo expression and demethylation of the corresponding promoter in a subset of hyporesponsive NK cells.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, we cannot exclude that some NK cells have received in vivo an additional signal leading to the initiation of KIR expression and that cytokines would only promote the preferential expansion of this committed subset in vitro. However, a recent report from Cichocki et al demonstrated that IL-15 or IL-2 induce c-Myc binding to an upstream distal KIR promoter element that promotes KIR transcription [14], supporting the idea that cytokines are directly required for induction of KIR expression and do not only allow the proliferation/differentiation of a subset of committed NK cells. Even if we cannot rule out that further unknown signals might be required, our data clearly show that cytokines are essential to induce stable KIR de novo expression and demethylation of the corresponding promoter in a subset of hyporesponsive NK cells.…”
Section: Discussionmentioning
confidence: 93%
“…We recently found that myc binds to KIR promoters, driving expression. 33 Interestingly, myc expression is linked to M-CSFR signaling and myeloid development. 34 Recently, a thymic pathway of NK-cell development was shown in rodents.…”
mentioning
confidence: 99%
“…However, a further study suggested that AML has a general inhibitory influence on KIR expression in mature NK cells and that AML exerts its repressor function by binding directly to the promoter of the different KIR genes (Trompeter et al, 2005). Recently, it was reported that the transcription factor c-Myc upregulated KIR gene transcription through direct binding to an upstream distal promoter element in peripheral blood NK cells, and that IL-15 promoted this effect (Cichocki et al, 2009). It was suggested that the role of the traditional transcription factors in KIR gene expression is different from that in other genes.…”
Section: Transcriptional Factors Regulation Of Kirmentioning
confidence: 99%